Cymbopogon proximus Aqueous Extract for Green Synthesis of Silver Nanoparticles: Preparation, Characterization and Bioactivities Assessment - El-Shaimaa A. Rawash; Sayed Rashad; Dina A. Anwar; Heba R. Eid; Ghadir A. El-Chaghaby (Novel Research in Microbiology Journal, 2025)
This study aimed to explore the biosynthesis of silver nanoparticles (AgNPs) using Cymbopogon proximus (CP) extract; a medicinal plant with a rich phytochemical profile. The AgNPs were produced by mixing water extract of CP with 1 mM silver nitrate solution. The synthesized AgNPs were characterized using UV-Vis spectroscopy, dynamic light scattering (DLS), zeta potential analysis (ZP), and transmission electron microscopy (TEM). The antioxidant activity was determined using several assays, including total antioxidant activity (TAA), total phenolic content (TP), and total flavonoid content (TF). Chemical composition of the aqueous extract was determined using Gas Chromatography-Mass Spectrometry (GC-MS). The antimicrobial activity was evaluated using the disc diffusion method against several bacterial and fungal strains. Cytotoxicity was assessed on Wi38 human lung fibroblast cell line using the MTT assay. A color change and a surface plasmon resonance peak in the UV–Vis spectrum confirmed the production of AgNPs.. The nanoparticles (NP) were spherical, stable, and exhibited an average size of less than 100 nm. GC-MS analysis confirmed the existence of numerous bioactive chemicals, including piperitone, elemol, and β-eudesmol. AgNPs-CP and CP extract unveiled substantial antimicrobial activity against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Salmonella typhi, and Candida albicans. The highest inhibition zone diameter was observed against C. albicans (32 mm). Cytotoxic analysis revealed a dose-dependent response with an IC₅₀ value of 240.67 ± 4.2 µg/ mL, indicating moderate cytotoxic potential at higher concentrations. AgNPs synthesized using CP extract demonstrated promising antioxidant, antimicrobial, and cytotoxic properties. The findings of this study support the potential application of the AgNPs-CP as a preservative in food/ feed additives.